4(n-12)=12(4-n)

Simple and best practice solution for 4(n-12)=12(4-n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n-12)=12(4-n) equation:


Simplifying
4(n + -12) = 12(4 + -1n)

Reorder the terms:
4(-12 + n) = 12(4 + -1n)
(-12 * 4 + n * 4) = 12(4 + -1n)
(-48 + 4n) = 12(4 + -1n)
-48 + 4n = (4 * 12 + -1n * 12)
-48 + 4n = (48 + -12n)

Solving
-48 + 4n = 48 + -12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12n' to each side of the equation.
-48 + 4n + 12n = 48 + -12n + 12n

Combine like terms: 4n + 12n = 16n
-48 + 16n = 48 + -12n + 12n

Combine like terms: -12n + 12n = 0
-48 + 16n = 48 + 0
-48 + 16n = 48

Add '48' to each side of the equation.
-48 + 48 + 16n = 48 + 48

Combine like terms: -48 + 48 = 0
0 + 16n = 48 + 48
16n = 48 + 48

Combine like terms: 48 + 48 = 96
16n = 96

Divide each side by '16'.
n = 6

Simplifying
n = 6

See similar equations:

| -4/5=-1/4-5/6q | | (9x-4)(5x+5)= | | X^2-8=9x | | -7(-4-4x)-6=1+7x | | 3(x-7)-4(2+x)=3 | | -5qx+6qx(5x-6)-65qx=-66 | | f(-3)=15(-3)+4 | | v-2+5= | | 4(12-n)=12(n-4) | | 5x+3=-77 | | 2x+40+3x+20=180 | | 2x=1.67 | | -3y+8(1y+3)=7+9(-3-y) | | 42=8m+133333 | | t+1+-4t+8=21 | | 4LW=V | | 12+x=6.8 | | t+1-4t+8=22 | | 12+x=16.8 | | -5(-4x-10)=-70 | | 4x^3-16x^2+13x=0 | | x^3-16x^2+13x=0 | | 5x-2+4x+2=-18 | | 1y=2x-4 | | 2(6t-4)=22t-t+4 | | 10=4x^2-2x+8 | | 12+x=16-8 | | 15p+45=120 | | 3x+11=p | | 8=x+20 | | 3u+16=76 | | r^2+2r-63= |

Equations solver categories